Le réinvestissement de l’espace local par les mouvements mexicains : refuge après les impasses politiques ou creuset d’une nouvelle culture politique ? - Geoffrey Pleyers (Cahiers des Amériques Latines)
Through the course of the first decade of the xxi century, there have been numerous social movements in Mexico that have focused their efforts on a local level. This article highlights two factors that have facilitated this development : the political impasse due to the closure of the political system to the demands of numerous social sectors, and the strengthening of a culture that sees social change from a local level. The second part of the article highlights the potential impact of these local movements on improving the quality of life on their members and residents of these communities, and then points out some limitations inherent in the political culture in which most of these movements are active.